A Study on the Role of Social Media in Driving Innovation and Economic Growth: A Macroeconomic Perspective - Rokhadi (PT. LITERASI SAINS NUSANTARA, 2023)
The advancements in information and communication technology, particularly social media, have dramatically altered the business landscape. Social media has become a primary platform for social interaction, business communication, and information exchange, creating new opportunities for innovation and economic growth. The purpose of this research is to delve deeper into how the use of social media influences innovation and economic growth from a macroeconomic standpoint. This research employs a literature review methodology with a qualitative approach using descriptive analysis. Data for this study are sourced from Google Scholar spanning from 2008 to 2023. The findings indicate that social media has emerged as a major driving force in reshaping the global economic landscape through facilitating information exchange, brand image formation, relationships with resources and new opportunities, and shifting communication paradigms among governments, corporations, and society. Despite its significant potential to drive innovation and economic growth, social media also faces serious challenges such as trust and data privacy issues, the spread of misinformation, and digital access disparities. It is crucial to comprehensively understand the impact of social media on the dynamics of the global economy to take necessary steps in harnessing its positive potential while addressing associated challenges and risks.